Judgement strategies in determining risk acceptability. - Beckwith, Jo Ann E. (Curtin University, 1996)
Most risk perception research has focused on how people view the riskiness or acceptability of particular hazards. Less attention has been paid to how people determine whether or not the decisions taken by other parties (e.g., politicians, government agencies, industry, etc.) to address risk issues are acceptable decisions.After examining the structure of risk perception and acceptability, this study researched the judgement strategies which individuals employ when assessing the acceptability or unacceptability of risk related decisions. It also investigated whether or not individuals directly affected by risk related decisions utilise similar judgement strategies to those of individuals not directly affected by the same decisions. This provided insights as to the reasons why local communities often reject risk related decisions that others in the broader community consider acceptable.Questionnaire data were collected relating to a number of risk scenarios based on real world issues and decisions. The survey included Curtin University students, residents of a Perth suburb, and members of a resident action group involved in a local risk issue at the time of the study.Unlike previous studies of heterogeneous hazard sets, exploratory factor analyses of 8 hazard domains did not reveal a global factor structure that could represent the construct 'risk'. Instead, each of the hazard domains revealed a qualitatively different factor structure, highlighting the context specific nature of risk.Through the use of correlation, linear regression, and path analysis the relationship between perceived riskiness, risk acceptability and other risk attributes or characteristics was explored. These analyses revealed that a relationship between perceived risk and risk acceptability exists to varying but significant degrees across different types of hazards. For a specific risk item, only a limited number of characteristics appear to significantly influence perceived risk or acceptability with some characteristics influencing both.Respondents used a ranking and weighting procedure to indicate the relative importance of the various qualitative characteristics in determining the acceptability of risk related decisions. This analysis revealed that people utilise both the characteristics of a risk issue as well as aspects of the decision itself when assessing the acceptability of risk related decisions. The study suggests that individuals who are not directly affected by specific decision employ simple judgement strategies not that dissimilar to those of the risk experts. This contrasts with directly affected individuals who appear to employ additional considerations, such as the trust worthiness of the decision makers, when assessing the acceptability of decisions.The thesis identifies a number of areas of future research, such as the role of hazard prototypes, and explores the implications of the study's findings for future risk communication efforts.